Global risk and contingency management research in times of crisis - Vajjhala, Narasimha, 1978-; Strang, Kenneth David, 1962- (Advances in logistics, operations, and management science (ALOMS) book series., 2022)
"This book provides an interdisciplinary approach to risk and contingency management, presenting work of researchers and practitioners that provides best practices and a look into the future of this field"--